Doctrine as a principle of protecting violated civil rights - Ivan Ivanets (Clío, 2025)
This article examines the role of legal doctrine as a principle in protecting civil rights that have been violated across jurisdictions. It focuses on the conceptual elevation of doctrine from interpretive guidance to a normative principle grounded in authoritative scholarship and established legal schools. The study employs doctrinal, comparative, and case law analysis, as well as quantitative methods. Results demonstrate that while doctrine is not legally binding, it functions as a legal principle guiding courts, especially in systems with limited codified norms. Doctrines were cited in 25% of civil rights cases and were used 1.84 times more often in common law jurisdictions. Historically, the identification of doctrine with principle stems from legal-philosophical developments in European jurisprudence, where doctrine shaped judicial coherence. The article supports the harmonization of doctrinal and principled reasoning to enhance civil rights protection and suggests further research on the convergence of national doctrines with international legal norms.